FEATURES OF THE STRUCTURE OF THE EPITHELIUM OF THE MUCOUS MEMBRANE OF THE TONGUE UNDER THE EFFECT OF COMPLEX OF FOOD ADDITIVES IN THE EXPERIMENT - Koka, V.M.; Starchenko, I.I.; Mustafina, G.M.; Roiko, N.V.; Filenko, B.M.; Proskurnia, S.A. (World of Medicine and Biology, 2022)
The paper was aimed at the study of the features of the structural organization of the covering epithelium of the mucous membrane of dorsal surface of the tongue of albino rats under the conditions of consumption of complex of food additives, supplemented into the ration, for 4 weeks. The study was performed on 30 outbred albino rats, both male and female, weighing 204±0.67 g. The standard ration of the experimental animals was supplemented with a complex of food additives: monosodium glutamate, Ponceau 4R and sodium nitrite for 1 and 4 weeks. The analysis of the structure of the epithelium of the mucous membrane of the tongue was performed on the conventional histological specimens and semi-thin sections. It has been established that consumption of complex of food additives supplemented into the standard ration of white rats for 4 weeks leads to a progressive thickening of the stratified squamous epithelium of the entire dorsal surface of the tongue and is accompanied by hydropic dystrophy, acanthosis, hyperkeratosis, focal stratification disorder.
Keywords: food additives; mucous membrane; stratified squamous epithelium; the tongue; albino rats